Hadith and Islamic Entrepreneurship Education (Edupreneurship) - Ahmad Roni Maulana Setiawadi; Ahmad Mohammad Tidjani; Abdul Kirom (Al-Alim: Jurnal Pendidikan Agama Islam, 2026)
The hadiths of the Prophet Muhammad are the second pillar after the Holy Qur'an as a barometer of human life in carrying out their activities. Fifteen centuries ago, the Messenger of Allah conveyed the importance of a stable world order as a support for the propagation of Islam and religion, so that it is not only strong mentally and psychologically, but also financially. This discussion reveals and explores the Hadiths of the Prophet that focus on edupreneurship in Islamic education, professionalism, business and trade dominance, the implementation of social norms contained in the Hadiths on entrepreneurship, the study of edupreneurship in Islamic boarding schools along with the role of the Prophet's Hadith in developing and producing a generation that is generous and independent, who are not only spiritually intelligent but also socially intelligent. This discussion is intended to be a contribution of ideas and a reference in matters related to edupreneurship based on the Prophet's Hadith.